2012
DOI: 10.3164/jcbn.12-18
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative and anti-inflammatory effects of spirulina on rat model of non-alcoholic steatohepatitis

Abstract: The pathogenesis of nonalcoholic steatohepatitis (NASH) remains unclear, but accumulating data suggest oxidative stress and the relationship between inflammation and immunity plays a crucial role. The aim of this study is to investigate the spirulina, which is a blue-green algae rich in proteins and other nutritional elements, and its component-phycocyanin effect on a rat model of NASH. NASH model rats were established by feeding male Wistar rats with choline-deficient high-fat diet (CDHF) and intermittent hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 50 publications
3
40
1
Order By: Relevance
“…Consequently, we would suggest an inhibition of the TLR4-dependent inflammation in liver tissue after Spirulina supplementation, which would reflect an enhancement of the hepatic immune response. Such a result has been already described in a rat model of NASH in which Spirulina administration inhibited NASH progression through antioxidative and anti-inflammatory mechanisms [31]. Given that the liver and gut are connected through the portal vein, we can speculate that anti-inflammatory effects of Spirulina in the liver may be dependent on improvements of the gut immune system or changes in gut barrier function via the production of AMPs [9,13].…”
Section: Discussionsupporting
confidence: 64%
“…Consequently, we would suggest an inhibition of the TLR4-dependent inflammation in liver tissue after Spirulina supplementation, which would reflect an enhancement of the hepatic immune response. Such a result has been already described in a rat model of NASH in which Spirulina administration inhibited NASH progression through antioxidative and anti-inflammatory mechanisms [31]. Given that the liver and gut are connected through the portal vein, we can speculate that anti-inflammatory effects of Spirulina in the liver may be dependent on improvements of the gut immune system or changes in gut barrier function via the production of AMPs [9,13].…”
Section: Discussionsupporting
confidence: 64%
“…For example, the spirulina alga had anti-oxidative and anti-inflammatory effects when assessed using a non-alcoholic steatohepatitis model [15]. C-phycocyanin [17], a biliprotein isolated from Spirulina platensis , suppressed inflammation by inhibiting the production of pro-inflammatory cytokines and by inhibiting the expressions of inducible nitric oxide synthase and cyclooxygeanase-2 [89].…”
Section: Anti-inflammatory and Antinociceptive Properties Of Marine Amentioning
confidence: 99%
“…Studies on the bioactivities of marine algae have revealed numerous health-promoting effects, including anti-oxidative, anti-inflammatory, antimicrobial, and anti-cancer effects. This mini-review will evaluate the specific effects found with red (Rhodophyta) [7-11], green (Chlorophyta) [12,13], brown (Phaeophyta) [14], and blue-green [15-18] species of marine algae. Figure 1 provides a brief overview of this mini-review.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant and anti-inflammatory properties from Spirulina and Chlorella compounds have been highlighted by in vitro and in vivo studies (Vijayavel et al, 2007;Cherng et al, 2010;Pak et al, 2012). A greater villus height in the jejunum of pigs receiving diets supplemented with Spirulina and Chlorella could result from a reduction in mucosal damage caused by oxidative stress (Zhu et al, 2012) or local inflammation after weaning, and explain the increased nutrient digestibility in trial 2.…”
mentioning
confidence: 99%